3 PENGARUH SUHU OVEN DALAM PEMANGGANGAN TERHADAP KUALITAS KUE SUS - Tresia, Nesya; Elida, Elida; Faridah, Anni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aims to analyze the effect of oven temperature (180â°c, 200â°c, and 220â°c) in baking towards soes quality in terms of volume, shape, aroma, texture, and taste. The type of this study was a pure experiment by using a complete randomized design method of three repetitions. Types of data used were primary data which was gathered from 15 panelists who provided answers from questionnaires (organoleptic test format). The data that have been obtained were tabulated and analyzed by variant (ANAVA). If it was different, it was proceeding with Duncan test. The results showed that there was a significant influence on sub-indicator of brownish yellow color quality, fragrant margarine aroma, soft texture, cavity texture. The results of the sub-indicator on the volume, shape, and taste of soes did not have a significant effect on the quality of the soes with different oven temperature. The best result in this study was 180â°c oven temperature.Keywords: Oven Temperature, Soes, Quality.